2011
DOI: 10.1080/22311866.2011.10719069
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity ofRosa damascenaMill Essential Oil

Abstract: Rosa damascena Mill. a plant from Rosaceae family is traditionally used for treatment of many disorders especially against infectious diseases. The antimicrobial activity of R. damascena oil was determined against a large number of microorganisms including Gram positive and Gram negative bacteria, yeast and filamentous by micro broth dilution assay. The oil was analyzed by GC and GC-MS. Chemical composition of oil revealed the presence of β-citronellol (48.2 %), geraniol (17.0 %), β-phenylethyl benzoate (5.4 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Vesicatoria 23 , Chromobacterium violaceum and Erwinia carotovora strains, 13 Staphylococcus aureus , 24 Bacillus cereus , Staphylococcus epidermidis , Pseudomonas fluorescens . 18 Pseudomonas aeruginosa 10 , 24 , 25 , Escherichia coli , Proteus vulgaris , Klebsiella pneumoniae , Candida albicans , Enterococcus faecalis , 24 Enterococcus faecium and Salmonella typhimurium 24 , 25 were less sensitive to rose essential oil. Bulgarian rose oil has been shown no antimicrobial activity.…”
Section: Modern Research On R Damascenamentioning
confidence: 99%
“…Vesicatoria 23 , Chromobacterium violaceum and Erwinia carotovora strains, 13 Staphylococcus aureus , 24 Bacillus cereus , Staphylococcus epidermidis , Pseudomonas fluorescens . 18 Pseudomonas aeruginosa 10 , 24 , 25 , Escherichia coli , Proteus vulgaris , Klebsiella pneumoniae , Candida albicans , Enterococcus faecalis , 24 Enterococcus faecium and Salmonella typhimurium 24 , 25 were less sensitive to rose essential oil. Bulgarian rose oil has been shown no antimicrobial activity.…”
Section: Modern Research On R Damascenamentioning
confidence: 99%
“…It is reported that its flowers especially contain essential oil, anthocyanin, flavonoid, tannin, and phenolic acid [13][14][15][16][17][18][19]. It has displayed diverse biological and pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-inflammatory, neuroprotective, antidepressant, antidiabetic, antiplasmodial effects of them have been shown in animal models [22,[24][25][26][27]. Biological activities such as anticancer, anticholinesterase, anti-inflammatory, antimicrobial, antioxidant of essential oils obtained from the flowers have been studied [15,18,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…This fragrant rose is a member of a few rose species produced commercially for oil, hips, concrete, absolute, and rose water (Mahboubi, 2016). The available literature has revealed that rose oil shows antioxidant (Yassa et al, 2009), antibacterial (Ulusoy et al, 2009), antifungal (Mahboubi et al, 2011) and anticancer (Zu et al, 2010) activities. The components of rose oil vary in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%